2002
DOI: 10.1152/ajpcell.00538.2001
|View full text |Cite
|
Sign up to set email alerts
|

Astrocytes from Na+-K+-Clcotransporter-null mice exhibit absence of swelling and decrease in EAA release

Abstract: We reported previously that inhibition of Na(+)-K(+)-Cl(-) cotransporter isoform 1 (NKCC1) by bumetanide abolishes high extracellular K(+) concentration ([K(+)](o))-induced swelling and intracellular Cl(-) accumulation in rat cortical astrocytes. In this report, we extended our study by using cortical astrocytes from NKCC1-deficient (NKCC1(-/-)) mice. NKCC1 protein and activity were absent in NKCC1(-/-) astrocytes. [K(+)](o) of 75 mM increased NKCC1 activity approximately fourfold in NKCC1(+/+) cells (P < 0.05… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
160
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 165 publications
(171 citation statements)
references
References 42 publications
11
160
0
Order By: Relevance
“…Genetic ablation of NKCC1, as well as its block by bumetanide,17 causes a decrease in intracellular Cl − in hypoxic neurons145 and blocks Na + -and Cl − -mediated cell swelling in astrocytes. 101,142,143 In vivo studies have shown that intracerebral bumetanide administered via a microdialysis probe, either prior to or during ischemia/hypoxia insult caused by temporary MCA occlusion, is neuroprotective, ameliorates brain damage, and reduces brain edema in rat focal ischemia,141,172,173 reinforcing the in vitro data. Focal cerebral ischemia in rats results in elevated NKCC1 protein levels in the ipsilateral cortex and striatum.…”
Section: The Nkcc Channelmentioning
confidence: 82%
“…Genetic ablation of NKCC1, as well as its block by bumetanide,17 causes a decrease in intracellular Cl − in hypoxic neurons145 and blocks Na + -and Cl − -mediated cell swelling in astrocytes. 101,142,143 In vivo studies have shown that intracerebral bumetanide administered via a microdialysis probe, either prior to or during ischemia/hypoxia insult caused by temporary MCA occlusion, is neuroprotective, ameliorates brain damage, and reduces brain edema in rat focal ischemia,141,172,173 reinforcing the in vitro data. Focal cerebral ischemia in rats results in elevated NKCC1 protein levels in the ipsilateral cortex and striatum.…”
Section: The Nkcc Channelmentioning
confidence: 82%
“…In this regards, astrocytic NKCC1 protein could function in clearing off excessive [K þ ] o . 104,105 Indeed, a short interval of anoxia/ischemia raises extracellular [K þ ] to B60 mmol/ L 106 and NKCC1 contributes to K þ influx into the cell. The activity of NKCC1 is involved not only in the control of extracellular K þ but also of extracellular Ca 2 þ ions.…”
Section: Namentioning
confidence: 99%
“…In a rat model of cerebral ischemia, NKCC1 transcripts and protein are significantly upregulated in cortical neurons, as well as in whole brain lysates [54,55]. These changes may occur in ischemic conditions secondary to elevated extracellular potassium and glutamate levels, substances known to stimulate NKCC1 activity in neurons and neuroglia [18,56,57]. Cytokines may also be involved in ischemiainduced upregulation of NKCC1, with interleukin-6 shown to activate NKCC1 in capillaries [58].…”
Section: Nkcc1mentioning
confidence: 99%